The summer deal : a novel - Shalvis, Jill (Shalvis, Jill. Wildstone novels., 2020)
Brynn heads back home for a fresh start and to lick her wounds. Kinsey, her long-time frenemy, has her own battles and secrets she's keeping from Brynn. Eli, Kinsey's best friend and Brynn's childhood crush, is funny and sexy and has a proposition for Brynn. As the long days of summer wind down, the three of them must discover if forgiveness is enough to grasp the unconditional love that's right in front of them.